Porting of the transfer-matrix method for multilayer thin-film computations on graphics processing units - Limmer, Steffen; Fey, Dietmar (Optical Engineering, 2013)
Thin-film computations are often a time-consuming task during optical design. An efficient way to accelerate these computations with the help of graphics processing units (GPUs) is described. It turned out that significant speed-ups can be achieved. We investigate the circumstances under which the best speed-up values can be expected. Therefore we compare different GPUs among themselves and with a modern CPU. Furthermore, the effect of thickness modulation on the speed-up and the runtime behavior depending on the input data is examined. © 2013 Society of Photo-Optical Instrumentation Engineers.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD3.portin_7